2019
DOI: 10.3389/fpsyg.2019.02553
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish Body Image State Scale: Factor Structure, Reliability and Validity in a Colombian Population

Abstract: ObjectiveBody image is a construct highly dependent on culture and ethnicity. Furthermore, recent studies reveal that body image is not only a trait, but also a momentary state subject to change in diverse situational contexts. However, cultural influences on momentary body image have not been sufficiently investigated. To assess the influence of Latin American culture on momentary body image and to enable its comparison to Western countries, the Spanish translation of an existing state body image scale such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
1
11
0
2
Order By: Relevance
“…It was expected here that a French version of the BISS would negatively correlate with measures of body dissatisfaction, social comparison, and eating symptomatology, and would present a single-factor structure, as demonstrated in relevant research (Mebarak Chams et al, 2019). Moreover, we wished to replicate differences between BMI groups and eating disorder symptomatology groups found in the Mebarak Chams ( 2019) study; it is expected that higher BMI categories will have a lesser French Body Image State Scale (F-BISS) score than lower BMI groups.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…It was expected here that a French version of the BISS would negatively correlate with measures of body dissatisfaction, social comparison, and eating symptomatology, and would present a single-factor structure, as demonstrated in relevant research (Mebarak Chams et al, 2019). Moreover, we wished to replicate differences between BMI groups and eating disorder symptomatology groups found in the Mebarak Chams ( 2019) study; it is expected that higher BMI categories will have a lesser French Body Image State Scale (F-BISS) score than lower BMI groups.…”
Section: Introductionmentioning
confidence: 82%
“…Convergent validity has been tested using the BSQ (Cooper et al, 1987), and the EDE-Q (Fairburn and Beglin, 1994). Validation studies have shown very good psychometric qualities (Cash et al, 2002;Mebarak Chams et al, 2019). The BISS appears to have a single-factor structure, with every item loading on the main factor at a >0.75 coefficient (Mebarak Chams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations